Get rid of ‘dis’ syndrome - Abd Razak, Dzulkifli (2006)
In a season that encourages giving and sharing, it is rather disappointing to read a comment by the chairperson of the Disabled Persons' Integrated Family Services saying companies are "not interested" in hiring disabled persons (orang kurang upaya). It has resulted in 80 per cent of them being without jobs. The others are either selfemployed or forced to accept lowpaying jobs. This is despite the suggestion that one per cent of the workforce in every company be made up of the disabled. Up to 100,000 of them have to rely on aid from the Welfare Department. The situation is described as "alarming". So much for Malaysians with a big heart! "Dis" has caused much discomfort to many, no matter how "normal" one looks or behaves.